2022
DOI: 10.3390/genes13050810
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Pseudogenes Suggest Repeated Inter-Species Hybridization among Direct Human Ancestors

Abstract: The hypothesis that the evolution of humans involves hybridization between diverged species has been actively debated in recent years. We present the following novel evidence in support of this hypothesis: the analysis of nuclear pseudogenes of mtDNA (“NUMTs”). NUMTs are considered “mtDNA fossils” as they preserve sequences of ancient mtDNA and thus carry unique information about ancestral populations. Our comparison of a NUMT sequence shared by humans, chimpanzees, and gorillas with their mtDNAs implies that,… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 64 publications
1
7
0
Order By: Relevance
“…We detect the largest numbers of numts both in count and length in H. sapiens , consistent with previous studies of human genomes ( Jensen-Seaman et al, 2009 ; Lang et al, 2012 ; Dayama et al, 2014 ; Dayama et al, 2020 ; Popadin et al, 2022 ). Three marsupial genomes: A. flavipes and S. harrisii , both in the family Dasyuridae and the extinct T. cynocephalus ( Figure 5 ), have high numt counts.…”
Section: Discussionsupporting
confidence: 92%
“…We detect the largest numbers of numts both in count and length in H. sapiens , consistent with previous studies of human genomes ( Jensen-Seaman et al, 2009 ; Lang et al, 2012 ; Dayama et al, 2014 ; Dayama et al, 2020 ; Popadin et al, 2022 ). Three marsupial genomes: A. flavipes and S. harrisii , both in the family Dasyuridae and the extinct T. cynocephalus ( Figure 5 ), have high numt counts.…”
Section: Discussionsupporting
confidence: 92%
“…This ‘distribution skew’ turns into ‘synonymity skew’ because NUMT-derived SNVs are highly synonymous ( Suppl. Note 3, see also (Popadin et al, 2022) 8 ). An excess of synonymous NuMT-derived SNVs in the contaminated late sample naturally led to a significant overestimation of the synonymity of late PGC mutations, and to an unsubstantiated claim of purifying selection in late PGCs.…”
Section: Resultsmentioning
confidence: 87%
“…Analyses of human, chimpanzee and gorilla genomes show that divergence between these lineages was much more complicated than previously supposed (Mailund 2012, Patterson et al 2006, Popadin et al 2022, Rogers and Gibbs 2014. Patterson et al (2006) suggest that "the hominin and chimpanzee lineages initially separated but then exchanged genes before finally separating less than 6.3 Myr ago" (p.1106).…”
Section: Initial Divergence Of Gorilla Pan Homomentioning
confidence: 99%
“…Cechova et al (2020) analyzed the male specific regions (MSY) of all great apes and found that the Y chromosomes of humans and gorillas were more similar than those of humans and chimpanzees, despite the latter sharing a more recent common ancestor. Furthermore, the presence of a pseudogene on chromosome 5 (ps5) of gorillas, chimpanzees, and humans points to a distant interspecies hybridization that occurred approximately 6.0 Ma, independently between the three diverging lineages (Popadin et al 2022). This pseudogene is speculated to have come from a hominine species (now extinct) that would have already diverged from a shared common ancestor.…”
Section: Initial Divergence Of Gorilla Pan Homomentioning
confidence: 99%